2009: el año de los desaciertos - Sarmiento, Eduardo (Diario El Espectador, 2010)
El Gobierno se empecinó en asegurar que Colombia estaba blindada contra la crisis económica mundial. El país no ha logrado superar la vulnerabilidad que dejó el cierre de los mercados internacionales.

The Government insisted on ensuring that Colombia was protected against the global economic crisis. The country has not managed to overcome the vulnerability left by the closure of international markets.
Keywords: Economía - Colombia; Crisis económica - Colombia; Política monetaria - Colombia; Política económica - Colombia; Economy - Colombia; Economic crisis - Colombia; Monetary policy - Colombia; Economic policy - Colombia